Pengaruh Employee Stock Option Program (ESOP) Terhadap Kinerja Perusahaan - Rahmi Rahmi; Erly Mulyani (Universitas Negeri Padang, 2019)
This study aims to analyze the influence in the form of increasing the performance of the company with the ESOP and to test the differences in performance before and after the application of the Employee Stock Option Program (ESOP). This research is classified as descriptive analysis research. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2013-2018. With the purposive sampling method, there were 17 companies as the research sample for descriptive analysis and 11 companies for the paired sample test because the data did not pass the normality test so that the Wilcoxon test was used as an alternative to the paired sample test. The company's performance variables are measured using Return On Equity (ROE), while the test variables are different measured by Return On Assets (ROA), Net Profit Margin (NPM), Sales Growth, Debt To Equity Ratio (DER). The type of data used is secondary data obtained from www.idx.co.id. The analytical method used is descriptive analysis and Wilcoxon test. The results of this study indicate that an increase in corporate performance shows fluctuating performance results with the ESOP, while differences in company performance before and after ESOP indicate that there are no differences in ROA, NPM, Sales Growth before and after ESOP, there are differences in DER before and after ESOP